(untitled) (International Journal of Engineering and Computer Science, 2017)
Communication has become indispensable in the modern world and antennas, being the electronic eyes and ears of the world, have become an integral part of our communication technologies. Among the various types of available antennas, Microstrip Antennas have been one of the most innovative developments in the era of miniaturization and are increasingly finding applications in a wide range of microwave systems. The aim of this paper is to design and compare the performance of Rectangular and Circular Microstrip Patch array antenna using ADS (Advance Design System) Momentum. Microstrip Line feed is used to feed each element. The performance is further enhanced by replacing the Microstrip Line feed by Aperture coupling since aperture coupling eliminates the direct electrical connection between the feed and patch and allows independent optimization of both the feed and radiating patch, improving radiation pattern and bandwidth. These arrays are designed to operate at a frequency of 2.4 GHz. Various parameters like the Return Loss, two dimensional and three dimensional radiation patterns, Gain and Directivity of the designed antenna are obtained using ADS Momentum for three designs, using different substrates. The purpose of this antenna is to obtain a high gain with better band width and reduced losses, to be especially used for WLAN applications.